Hubungan Faktor Psikologis dengan Atrium Fibrilasi: Suatu Tinjauan Kepustakaan - Murni, Arina Widya; Fadella, Annesa (UI Scholars Hub, 2025)
Psychological factors influence the onset of cardiac rhythm and dysrhythmia disorders, including atrial fibrillation (AF), which is defined as uncoordinated atrial activation resulting in ineffective contractions. Psychological factors have a bidirectional relationship with AF, as AF symptoms can lead to a decline in mental health, which in turn negatively affects the clinical course. One explanation for how psychological stress impacts the heart and contributes to AF involves the autonomic nervous system and the hypothalamic-pituitary-adrenal (HPA) axis. Anxiety and depression are common comorbidities in AF. These conditions can be assessed using standardized instruments, such as the Hospital Anxiety and Depression Scale (HADS), which includes subscales for anxiety (HADS-A) and depression (HADS-D). Additionally, the Beck Depression Inventory (BDI) can be used to assess depression, while the State-Trait Anxiety Inventory (STAI) is useful for evaluating anxiety. Management of psychosomatic disorders requires a bio-psycho-socio-spiritual approach, involving both non-pharmacological and pharmacological therapies. Key components include somatic or symptomatic therapy, psychotherapy or sociotherapy, and psychopharmacotherapy, with the choice of method depending on various factors. In AF patients, treatment of psychological stress, anxiety, and depression generally prioritizes non-pharmacological approaches, such as supportive psychotherapy. If necessary, short-term use of benzodiazepines as anti-anxiety medication can be considered. In cases requiring antidepressants, newer agents such as selective serotonin reuptake inhibitors (SSRIs) are preferred, with close monitoring of heart rhythm due to the potential arrhythmogenic effects of certain medications, especially non-selective antidepressants.